THE EVOLUTION OF SPORT PSYCHOLOGY STUDIES IN BASKETBALL: A BIBLIOMETRIC APPROACH TO GLOBAL PUBLICATIONS - Hanafi, Muhammad Syahru Ramadhan; Mustika Fitri; Hamidi, Ahmad; Apriady, Hilmy (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Research in the field of sport psychology, especially in basketball, has grown rapidly in the last decade. This study examines the trends and evolution of research in basketball sport psychology through a bibliometric analysis approach. With a total of 905 articles analyzed from 2014 to 2024, this study aims to understand the development of the research focus and its contribution to the discipline. Through bibliometric analysis of data obtained from the Scopus database, we investigated scientific publications related to sports psychology in basketball. VOSViewer software facilitated the visualization of collaboration networks between researchers, institutions, and research topics, thus providing a deeper understanding of the structure and dynamics within this field of study. The bibliometric methods used in this study provided insights into research trends over time, identified key topics of interest to scholars, and highlighted contributions from leading institutions and researchers in the field of sport psychology in basketball. This study emphasizes the importance of ongoing research and collaboration in developing a deeper understanding of the psychological aspects of basketball. In addition, the study included a systematic literature review to map out potential areas of future research based on current trends. As such, this study offers a comprehensive guide for future research in the field of sport psychology in the context of basketball, which can benefit coaches, athletes, and academics interested in the mental aspects of the sport